Mismatch negativity and P3a amplitude in young adolescents with first-episode psychosis: a comparison with ADHD. Issue 2 (25th October 2016) - Rydkjær, J.; Møllegaard Jepsen, J. R.; Pagsberg, A. K.; Fagerlund, B.; Glenthøj, B. Y.; Oranje, B.
Abstract : Background: Deficient mismatch negativity (MMN) has been proposed as a candidate biomarker in schizophrenia and may therefore be potentially useful in early identification and intervention in early onset psychosis. In this study we explored whether deficits in the automatic orienting and reorienting responses, measured as MMN and P3a amplitude, are present in young adolescents with first-episode psychosis (FEP) and whether findings are specific to psychosis compared to young adolescents with attention deficit hyperactivity disorder (ADHD). Method: MMN and P3a amplitude were assessed in young adolescents (age 12–17 years) with either FEP ( N = 27) or ADHD ( N = 28) and age- and gender-matched healthy controls ( N = 43). The MMN paradigm consisted of a four-tone auditory oddball task with deviant stimuli based on frequency, duration and their combination. Results: Significantly less MMN was found in patients with psychosis compared to healthy controls in response to frequency and duration deviants. MMN amplitudes in the group of patients with ADHD were not significantly different from patients with psychosis or healthy controls. No significant group differences were found on P3a amplitude. Conclusion: Young adolescents with FEP showed impaired MMN compared to healthy controls while intermediate and overlapping levels of MMN were observed in adolescents with ADHD. The findings suggest that young FEP patients already exhibit pre-attentive deficits that are characteristic of schizophrenia albeit expressed on a continuum shared with other neuropsychiatric disorders.